Investigating the Impact of Patient Education and Self-Management Programs in Reducing the Burden of Chronic Postoperative Pain: Patient Education and Self-Management Programs in CPSP - Aziz, Munazzah; Iftikhar, Maryam; Haider, Sohaib; Siddique, Samreen; Barkat, Maryam; Munawar, Sidra; Ejaz, Maheen; Ahsan, Shaharyar (Pakistan Journal of Health Sciences, 2025)
Chronic postsurgical pain (CPSP) remains a significant clinical challenge, as many patients experience severe pain after surgery and find conventional management strategies inadequate. These complications adversely affect patients’ quality of life, underscoring the need for effective self-management methods. Objectives: To investigate the impact of Patient Education and Self-Management Programs in reducing the burden of chronic postoperative pain. Methods: A systematic review was conducted of all studies currently published between 2013 and 2023 examining various patient education and self-management interventions for chronic postoperative pain. Data were extracted from relevant studies to assess the effectiveness of these programs across different surgical procedures and follow-up periods. Results: The review indicates that interventions such as structured patient education, relaxation exercises, device-assisted therapies, and telehealth applications show promise in reducing CPSP. Compared to control groups, participants who received these interventions reported superior health outcomes and lower levels of discomfort. The benefits were observed across diverse surgical contexts and timeframes. Conclusions: It was concluded that tailored patient education and self-management programs play a crucial role in alleviating chronic post-surgical pain, enhancing patient satisfaction, and reducing healthcare costs.